2015
DOI: 10.1016/j.jocd.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A Trimodality Comparison of Volumetric Bone Imaging Technologies. Part III: SD, SEE, LSC Association With Fragility Fractures

Abstract: Part II of this 3-part series demonstrated 1-yr precision, standard error of the estimate, and 1-yr least significant change for volumetric bone outcomes determined using peripheral (p) quantitative computed tomography (QCT) and peripheral magnetic resonance imaging (pMRI) modalities in vivo. However, no clinically relevant outcomes have been linked to these measures of change. This study examined 97 women with mean age of 75 ± 9 yr and body mass index of 26.84 ± 4.77 kg/m 2 , demonstrating a lack of associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Nevertheless, these apparent micro-architecture traits differ substantially from traits obtained via high-resolution pQCT (117) , and at this time there seems to be no additional diagnostic value, or clinical utility over standard pQCT-measured vBMD (121) .…”
Section: Voxel Size Selectionmentioning
confidence: 77%
“…Nevertheless, these apparent micro-architecture traits differ substantially from traits obtained via high-resolution pQCT (117) , and at this time there seems to be no additional diagnostic value, or clinical utility over standard pQCT-measured vBMD (121) .…”
Section: Voxel Size Selectionmentioning
confidence: 77%
“…Sixteen of 25 studies included women only, ( 10,11,18‐21,23,26‐31,34‐36 ) six studies men only, ( 12,13,22,24,32,37 ) and three studies both genders. ( 14,25,33 ) For ethnicity, the 25 studies included participants as follows: seven French, ( 10,13,18‐20,22,35 ) five American, ( 12,21,28,29,32 ) four Swedish, ( 24,27,31,37 ) two Canadian, ( 11,23 ) two British, ( 25,34 ) two multiple, ( 14,30 ) one Swiss, ( 36 ) one Asian, ( 26 ) and one Brazilian. ( 33 ) In summary, seven were from North America, one from South America, 14 from Europe, one from Asia, and two from multiple countries (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The full texts of 151 papers were retrieved for further assessment of eligibility; 126 papers were further excluded, because these studies did not involve fracture discrimination or prediction. Hence, 25 papers were finally included in this systematic review including 18 case–control studies ( 10 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ) and seven cohort studies. ( 11 , 12 , 13 , 14 , 35 , 36 , 37 ) Out of 25 papers, only 16 papers were included for meta‐analysis, in which there were 11 case–control studies ( 10 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ) and five cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For bone outcomes, we used analysis modes based on the study by Ashe, et al (26). We considered cortical thickness as the primary cortical structure outcome of interest since the study by Ashe et al demonstrated that cortical thickness was the cortical geometry measure with the greatest correlation with fracture load (R 2 =0.81, p<0.001) and previous studies identified associations with risk of fracture (27). Trabecular vBMD also correlates highly with fracture load (R 2 =0.72 P<0.001) (28, 29).…”
Section: Methodsmentioning
confidence: 99%